The Influence of Clinical Staff Competency, Change Management and Service Digitalization on The Innovation Performance of Health Service Units In A Modern Clinic - Ana Faizah; Fanny Anggraeni Octoviani; Djunaedi Djunaedi (Jurnal Ners, 2026)
The major consideration of the investigation is to find out the interaction of the competencies of clinical staff, the change agent, and the new technology together with the performance of a healthcare unit in the contemporary innovation-oriented clinical network. The study originates from the perception of the need for innovations and changes in the healthcare industry which is a very much the case for the modern clinical organizations that are to provide soon, excellent, and technology-based services. For the research, a quantitative explanatory strategy was used, along with a sample of 150 respondents made up of clinical and administrative staff, as well as operational managers from the modern clinical network. Deliberate or purpose sampling was the technique employed to select respondents based on their work experience, involvement in operations, and familiarity with digital service systems. The results of multiple linear regression analysis indicated that each of the three independent variables had a positive and significant impact on the innovation performance of the healthcare units. The coefficient of determination value indicates that the blend of clinical staff competency, change management, and service digitalization has a great impact on innovation performance. The research advocates the clinical staff training as an important tactic, in addition to establishing change management infrastructures, and speeding up the digitalization of services, for boosting the innovation in modern clinic networks.